SUSTAINABLE DEVELOPMENT OF UKRAINIAN CITIES IN THE CONTEXT OF GLOBALISATION: FOREIGN AND DOMESTIC APPROACHES - USHENKO, Natalya; TUPIKA, Alina (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article explores the concept of sustainable development of Ukrainian cities, with a particular focus on Kyiv, highlighting their adaptability, competitiveness, and the quality of life of their residents. Sustainable urban development is analyzed through the lens of resilience, emphasizing the ability to withstand risks and threats while ensuring long-term stability and growth through effective regional policies. The research presents a structural-functional model of sustainable development that integrates economic, social, and environmental dimensions while also incorporating external factors such as governance, peace, security, and cultural values.The impact of globalization on leading urban centers is examined, particularly how these cities form the core of global economic networks, influence technological innovation, drive green initiatives, and implement sustainability strategies. The study outlines the increasing integration of advanced and developing economies through foreign direct investments, the reduction of trade barriers, economic reforms, and migration flows. Both positive and negative aspects of globalization are identified, including enhanced economic cooperation, technological advancements, increased investment, as well as economic disparity, social polarization, and environmental degradation.A key focus of the research is the role of human capital, particularly in the wartime and post-war context of Ukraine. Human potential is identified as a crucial driver for sustaining economic activity, fostering innovation, and ensuring resilience against crises. The study highlights the importance of civic engagement and social participation in urban initiatives, which have become vital for the sustainable and adaptive development of cities. The transformation of public engagement in urban governance, shifting from cultural and environmental projects to humanitarian efforts and infrastructure restoration during wartime, is also analyzed.A major aspect of the research is the sustainable development trajectory of Kyiv as a model city. The study identifies structural imbalances, economic volatility, and environmental threats exacerbated by globalization and urbanization. It proposes strategies for leveraging human capital, social equity, and innovation-driven governance to build a sustainable urban environment. The findings underscore the significance of balancing globalization's advantages with strategies to mitigate its adverse effects, ensuring inclusive and adaptive urban development.The research also addresses the dynamic changes in urban social participation in Ukraine due to the ongoing war. Civic engagement has shifted dramatically from pre-war activities focused on cultural development and environmental sustainability to wartime efforts centered on humanitarian aid, military support, and infrastructure rebuilding. Data on public participation trends, volunteerism, and social initiatives demonstrate a substantial increase in local engagement, reflecting the resilience of Ukrainian society in times of crisis.A comparative analysis of public engagement before and during wartime is conducted, revealing an increase in voluntary initiatives, grassroots movements, and community-led urban transformation projects. The study illustrates how social cohesion and collective action have become fundamental to urban resilience and sustainable recovery efforts. Additionally, the paper highlights emerging mechanisms of participatory governance, such as digital consultation platforms and decentralized decision-making models, which have proven effective in strengthening civic involvement and ensuring inclusive urban development.The study concludes that sustainable urban development in Ukraine requires an integrated approach that balances economic, social, and environmental priorities while addressing the challenges posed by globalization. Strengthening institutional capacity, fostering human capital, and promoting innovative governance models are essential for ensuring long-term sustainability. The research highlights the need for policy frameworks that support green energy initiatives, circular economy practices, and socially inclusive development models to build resilient cities in Ukraine. The study also emphasizes the importance of international cooperation and knowledge exchange in advancing Ukraine’s urban sustainability agenda.
Keywords: society; globalisation; sustainable development; city; human potential; civic engagement; social participation; inclusiveness; innovation